THE INFLUENCE OF COOPERATIVE LEARNING MODEL TYPE TWO STAY TWO STRAY TO THE LEARNING OUTCOMES OF STUDENTS OF CLASS X BUILDING CONSTRUCTION ENGINEERING IN PROGRAM ENGINEERING DRAWINGS IN SMK NEGERI 1 PARIAMAN - 566-575 , Ulfa Widiya Kasih (CIVED, 2015)
Abstract The background of this research is the lack of student learning outcomes in subjects Building Materials. This study apply cooperative learning model type Two Stay Two Stray. The purpose of this study was to determine whether there is influence of cooperative learning model type Two Stay Two Stray to the learning outcomes of students of class X Building Construction engineering in program engineering drawings in SMK Negeri 1 Pariaman. This research includes a real experimental study with randomized Control Group Pretest-Posttest design. The population of this research were 78 students of class X which consists of 5 classes. The sample in this study selected two classes of grade X TGB 1 group B as experimental class, meanwhile X TGB 2 group D as the control class. The instruments used in this study is pretest and posttest in the form of 35 objective questions that have been tested for validity, reliability, power index of difficulty and difference of each questions. Data were analyzed using t-test (two average differences) that uses the value of the gain scores (the difference between the pretest and posttest). The results of this study showed that the experimental class has an average score of pretest was about 51,81 and posttest score was about 81,71. Meanwhile the control class has an average score of pretest was about 51,79 and posttest score was about 72,32. It can be seen that there is an increase in the learning outcomes of students in class at the experimental class. After the t test obtained t = 3,578 and t table = 2,045 at significance 0,05. So we can conclude that cooperative learning model type two stay two stray has significant influence towards learning outcomes in building construction subject. This research is recommended for SMK teachers to use cooperative learning model type Two Stay Two Stray in Building Construction course. Keywords: Two Stay Two Stray, Learning Outcomes, Building Construction